2009
DOI: 10.1364/ol.34.002498
|View full text |Cite
|
Sign up to set email alerts
|

Self-compression of millijoule 15 μm pulses

Abstract: We demonstrate a four-stage optical parametric chirped-pulse amplification system that delivers carrier-envelope phase-stable approximately 1.5 microm pulses with energies up to 12.5 mJ before recompression. The system is based on a fusion of femtosecond diode-pumped solid-state Yb technology and a picosecond 100 mJ Nd:YAG pump laser. Pulses with 62 nm bandwidth are recompressed to a 74.4 fs duration close to the transform limit. To show the way toward a terawatt-peak-power single-cycle IR source, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 16 publications
0
58
1
Order By: Relevance
“…At 1.8 m, FS provides significant negative GDD ͑−68 fs 2 / mm͒. Furthermore, in contrast to experimentally observed self-compression, 6,7,14,15 the laser power of 10 GW in our experiment is roughly two times below the estimated critical power for self-focusing.…”
Section: Fig 1 ͑A͒contrasting
confidence: 81%
“…At 1.8 m, FS provides significant negative GDD ͑−68 fs 2 / mm͒. Furthermore, in contrast to experimentally observed self-compression, 6,7,14,15 the laser power of 10 GW in our experiment is roughly two times below the estimated critical power for self-focusing.…”
Section: Fig 1 ͑A͒contrasting
confidence: 81%
“…This work opens the door for power scaling of OPCPA to simultaneously obtain a high peak power and an ultrashort pulse duration less than 100 fs. Following this pioneering work, Mucke et al [100] have demonstrated a 4-stage KTP/KTA OPCPA, which produce a CEP-stable multi-mJ 1.5-µm~70-fs pulse based on the fusion of a diode-pumped solid-state (DPSS) femtosecond Yb:KGW MOPA system and picosecond Nd:YAG solid-state technology. Even if the abovementioned works show the ability of generating IR output energy reaches the multi-mJ level in OPCPA, OPCPA in general faces important technical challenges [42], such as the requirement of a specific pump laser, the difficulty in synchronization with an external pump laser, and the unwanted generation of parasitic superfluorescence accompanying the primary pulse in broadband high-parametric-gain configurations [105].…”
Section: High-energy Dual-chirped-opa (Dc-opa)mentioning
confidence: 99%
“…The self-phase modulation (SPM) of an ultrashort pulse in HCF filled with gas can efficiently broaden the pulse spectrum, and after the dispersion compensation, the broadened spectrum can be recompressed to few-cycle durations. The HCF compression has manifested its validity in a number of previous research studies [97][98][99][100].…”
Section: Introductionmentioning
confidence: 99%
“…One solution are laser sources with high ponderomotive energy U p ∝ λ 2 I at moderate intensity level, i. e., IR CEP-stable few-cycle high-power laser systems. The present immense interest of the ultrafast community in high-U p sources [3][4][5][6][7][8][9][10][11] has three major reasons:…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present a hybrid Type-II IR OPCPA / filamentation approach to pursue a TW-peak-power single-cycle IR source [10,11] that will find many applications in attosecond and high-field science.…”
Section: Introductionmentioning
confidence: 99%